Epic Games v. Apple: Fortnite battle that can change the industry - Ambrasaitė, Paulina; Smagurauskaitė, Agnė (Vilnius University Open Series, 2021)
When Apple Store was launched, there were 500 applications available for iPhone users. Since then, the number of applications in the App Store skyrocketed and in 2017 reached around 2.2 million. In recent years, the number of apps in the App Store is steadily declining, due to Apple’s decision to remove old apps that do not function or the apps that do not follow current app guidelines. The distribution of the apps is only available through the App Store, where the only available payment processor is controlled by Apple. That places Apple in a unique position. The case Epic Games v. Apple raises a broader discussion, whether Apple as the “gatekeeper” of Apps can restrict distribution and access to the apps in the iOS operational system, and whether that kind of activity can be deemed as a monopolist and restrictive competition in App distribution market. This paper will analyze and critically evaluate the recent lawsuit that was brought up against Apple by Epic Games. The main aspect of this analysis is whether Apple can legally restrict the developer’s ability to distribute the applications through the App Store and if it does not restrict the competition. This article is composed of several chapters. Chapter one will examine the relevant facts of the Epic and Apple lawsuit and will summarize the key arguments of this case. The second chapter will explore the relevant legislation and the relevant market related to previously mention proceedings and will explain how the doctrine of the essential facility might affect the case. Chapter three will delve into similar cases brought up earlier and will cover the distribution of digital goods. Chapter four will provide conclusions and the paths moving forward. The object of the paper is to perform a detailed analysis of the case. The purpose of the paper is an assessment of the relevant facts and legal framework regarding Epic’s claim, as well as analyze the topics of foreclosure and dominance in the market. To write this paper several academic writing methods such as descriptive to provide readers with relevant legislation and inform them about relevant facts of the case, also analytical to form the readers’ opinions regarding the recent events and activities of both sides of the suit, also a comparative to compare different legal frameworks in the United States of America and European Union regarding the regulation of monopoly were used. There is no doubt this topic has enormous relevance because of its’ possible after-effects. Epic’s claim already has an impact not only on Apple but also on the whole app development and distribution industry of digital goods and might create a precedent to the similar cases. Currently, this claim is only discussed in the media, and there is no precedent. This article will not give a clear answer to how this lawsuit will be resolved, because it mainly depends on court interpretation of the relevant market. We would rather give a few alternative solutions to this case.